Doing narrative research - Andrews, Molly; Squire, Corinne 1958-; Tamboukou, Maria 1958- (Sage, 2013)
"Written by an international team of experts in the field, the second edition of this popular text considers both the theoretical underpinnings and practical applications of narrative research. The authors take the reader from initial decisions about forms of narrative research, through more complex issues of reflexivity, interpretation and the research context. Existing chapters have been updated to reflect changes in the literature and new chapters from eminent narrative scholars in Europe, Australia and the United States have been added on a variety of topics including narratives and embodiment, visual narratives, narratives and storyworlds, new media narratives and Deleuzian perspectives in narrative research. This book will be invaluable for all students, researchers and academics looking to use narrative methods in their own social research."--Publisher's website.